Case study and numerical modelling of heat transfer in a snow-covered building roof - Borui Zhang; Qingwen Zhang; Huamei Mo; Feng Fan (Case Studies in Thermal Engineering, 2022)
We explored the heat transfer in a snow-covered building roof by setting a prototype field measurement in Harbin during the winter of 2018. Several sets of data were measured, including the meteorological elements and snow properties. Hence, a temperature-dependent constitutive model for a heterogeneous medium, the deposited snow on the roof, was accordingly proposed. To validate this, this model was adopted in a new proposed 3-D finite element modelling (FEM), in ANSYS software, to quantitatively analyze the heat transfer process. All heat transfer patterns, including roof heat-loss conduction, surrounding turbulent exchange, and net radiation, as well as the involved phase-changes in snow metamorphism, were considered. Using the birth and death element technique, the snowmelt and subsequent ice-layer formation can also be visually reproduced. The feasibility of the FEM was validated by comparing both the snow metamorphic features and the hourly temperature gradient in the snow between the FEM and the prototype measurement. In future work, the influence of water vapor transport in snow and the range of time-scales should be increased in further studies.